Rekonstruksi Kriteria Kesahihan dan Penerapan Hadis Menurut Muh. Al- Gazali - Abustani Ilyas (Buletin Al-Turas, 2008)
Muh. Al-Gazali is a Muslim scholar who is brave to make criticism towards a group of society who less accepted "kehujjahan Hadis', 'itihad, and critical reinterpretation towards 'Hadis texts'that contained in Sahih Bukhari and Sahih Muslim books. This is made him accused as a sunnah refuse. The arise problem includes 'Hadis position', formulation of valid Hadis criteria, and how to interact with Prophet Hadis Methodology that is used in this discussion is pure descriptive. This research made the writing of al-Gazali as a primary source that much discuss about Hadis problems Al-Gazali considered that all Hadis could become 'hujjah', except 'Hadis ahad' that relates with faith and 'Hadis dhaif' about every things. On valid Hadis criteriais the same as by salaf Muslim Scholar, it is only added on the extem aspect ie, the carefulness in the processing of data and avoiding the repetitiveness of carnal desire. And the intern aspect,the meaning of Hadis must be the same as/parallel with Al-Quran contents